Investigation of phosphoproteome in RAGE signaling - Batkulwar, Kedar B.; Bansode, Sneha B.; Patil, Gouri V.; Godbole, Rashmi K.; Kazi, Rubina S.; Chinnathambi, Subashchandrabose; Shanmugam, Dhanasekaran; Kulkarni, Mahesh J. (Proteomics, 2015)
The receptor for advanced glycation end products (RAGE) is one of the most important proteins implicated in diabetes, cardiovascular diseases, neurodegenerative diseases, and cancer. It is a pattern recognition receptor by virtue of its ability to interact with multiple ligands, RAGE activates several signal transduction pathways through involvement of various kinases that phosphorylate their respective substrates. Only few substrates have been known to be phosphorylated in response to activation by RAGE (e.g., nuclear factor kappa B); however, it is possible that these kinases can phosphorylate multiple substrates depending upon their expression and localization, leading to altered cellular responses in different cell types and conditions. One such example is, glycogen synthase kinase 3 beta which is known to phosphorylate glycogen synthase, acts downstream to RAGE, and hyperphosphorylates microtubule-associated protein tau causing neuronal damage. Thus, it is important to understand the role of various RAGE-activated kinases and their substrates. Therefore, we have reviewed here the details of RAGE-activated kinases in response to different ligands and their respective phosphoproteome. Furthermore, we discuss the analysis of the data mined for known substrates of these kinases from the PhosphoSitePlus (http://www.phosphosite.org) database, and the role of some of the important substrates involved in cancer, diabetes, cardiovascular diseases, and neurodegenerative diseases. In summary, this review provides information on RAGE-activated kinases and their phosphoproteome, which will be helpful in understanding the possible role of RAGE and its ligands in progression of diseases.
Keywords: Cell biology; Disease; Glycation; Kinase; Phosphoproteome; RAGE

Targeted quantification of N-1-(carboxymethyl) valine and N-1-(carboxyethyl) valine peptides of beta-hemoglobin for better diagnostics in diabetes - Jagadeeshaprasad, Mashanipalya G.; Batkulwar, Kedar B.; Meshram, Nishita N.; Tiwari, Shalbha; Korwar, Arvind M.; Unnikrishnan, Ambika G.; Kulkarni, Mahesh J. (Clinical Proteomics, 2016)
Background: N-1-(Deoxyfructosyl) valine (DFV) beta-hemoglobin (beta-Hb), commonly referred as HbA1c, is widely used diagnostic marker in diabetes, believed to provide glycemic status of preceding 90-120 days. However, the turnover of hemoglobin is about 120 days, the DFV-beta-Hb, an early and reversible glycation product eventually may undergo irreversible advanced glycation modifications such as carboxymethylation or carboxyethylation. Hence quantification of N-1-(carboxymethyl) valine (CMV) and N-1-(carboxyethyl) valine (CEV) peptides of beta-Hb would be useful in assessing actual glycemic status. Results: Fragment ion library for synthetically glycated peptides of hemoglobin was generated by using high resolution-accurate mass spectrometry (HR/AM). Using parallel reaction monitoring, deoxyfructosylated, carboxymethylated and carboxyethylated peptides of hemoglobin were quantified in clinical samples from healthy control, pre-diabetes, diabetes and poorly controlled diabetes. For the first time, we report N-1-beta-valine undergoes carboxyethylation and mass spectrometric quantification of CMV and CEV peptides of beta-hemoglobin. Carboxymethylation was found to be the most abundant modification of N-1-beta-valine. Both CMV-beta-Hb and CEV-beta-Hb peptides showed better correlation with severity of diabetes in terms of fasting glucose, postprandial glucose and microalbuminuria. Conclusions: This study reports carboxymethylation as a predominant modification of N-1-beta-valine of Hb, and quantification of CMV-beta-Hb and CEV-beta-Hb could be useful parameter for assessing the severity of diabetes.
Keywords: Diabetes; Diagnosis; Glycation; Glycemic control; HbA1c; Mass spectrometry